The effects of redlining in Singapore’s red-light district - Zheng, Mo (International Journal of Strategic Property Management, 2018)
There are cities or regions with legal red-light districts in both developed and developing countries, but there are also regions or countries with no clear rules regarding prostitution. Financing issues in red-light districts represent another aspect rarely examined in the academic world. Most research studies about redlining are focused on racial or poverty levels, but this paper investigates it in relation to moral issues concerning vice activities. The objectives of this paper are to firstly analyse the red-light phenomenon in relation to sales prices and rent prices, secondly to test the redlining effect on property markets. This paper contributes to the current academic literature. The research setting of this paper is Geylang, Singapore, a place known for its centralized location, 24/7 stores, historic locales and prostitution-related business. The results indicate that the existence of Singapore’s red-light district has a negative effect on both residential purchase prices and rent levels. The results also indicate that there exists a redlining effect since the home prices have a much higher dis-count than rents.